Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/cdn/nzz025
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Intake, Fetal Brain Growth, and Maternal Smoking in Pregnancy: A Randomized Controlled Trial

Abstract: Background Folic acid supplementation during pregnancy plays an important role in fetal growth and development. To our knowledge, no experimental study has examined the effect of folic acid on fetal brain growth in women who smoke cigarettes during pregnancy. Objectives The aim of this study was to investigate the efficacy of higher-dose compared with standard-dose folic acid supplementation on prenatal fetal brain growth, measured by head circumference, brain weight, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The current US Preventive Services Task Force (USPSTF) recommendation is that all persons planning to become pregnant should take a daily supplement containing 0.4 to 0.8 mg of folic acid [ 10 ]. It has been shown that higher doses of folic acid (4mg) prevent reduction in fetal body size [ 11 ] and optimize brain growth [ 12 ] among infants of women who smoke tobacco during pregnancy [ 11 ]. Further research is needed to explore the effects of high-dose folic acid in specific populations, such as smokers and individuals with diabetes to reduce the risk of CHDs.…”
Section: Discussionmentioning
confidence: 99%
“…The current US Preventive Services Task Force (USPSTF) recommendation is that all persons planning to become pregnant should take a daily supplement containing 0.4 to 0.8 mg of folic acid [ 10 ]. It has been shown that higher doses of folic acid (4mg) prevent reduction in fetal body size [ 11 ] and optimize brain growth [ 12 ] among infants of women who smoke tobacco during pregnancy [ 11 ]. Further research is needed to explore the effects of high-dose folic acid in specific populations, such as smokers and individuals with diabetes to reduce the risk of CHDs.…”
Section: Discussionmentioning
confidence: 99%
“…Preconception folic acid supplement use increased foetal head size and cerebellar growth in three studies [34,36,45], but not in two other studies [46,48]. Folic acid supplement use at other time points had no effect on neonatal head size [37,43,44,47]. The majority of studies that assessed maternal folic acid supplementation disclosed that supplementation and food fortification, even after conception, ameliorated offspring neurodevelopment and reduced the risk of psychosis from infancy to childhood [78][79][80][81][82].…”
Section: Folic Acid Supplement Usementioning
confidence: 96%
“…Preconception, early and mid-trimester folic acid supplement use were not associated with neonatal HC in two studies [37,46]. An RCT by Yusuf et al reported that even high dose folic acid use (4 mg/day) during the first trimester among smokers had no significant effect on neonatal HC or brain weight at birth when compared to those who received the standard dosage (0.8 mg/day) [44]. However, folic acid supplement use in combination with iron from preconception onwards significantly increased HC at birth by 0.16 cm (B = 0.16, 95% CI −0.03; 0.34, P = 0.012) [45].…”
Section: Folic Acid Supplement Usementioning
confidence: 96%
“…Eryilmaz et al showed that the prenatal exposure of folic acid was associated with a cortical thickness increase in the bilateral, frontal, and temporal regions, as well as delayed age-associated cortical thinning in the temporal and parietal regions [ 34 ]. A randomized controlled trial (RCT) was performed to assess the effect of folic acid on fetal brain growth among pregnant women who smoke [ 35 ]. The results indicated that infants born to mothers who received high dose folic acid (4 mg/day) showed no difference in brain weight, but were 0.33 percentage points lower in brain/body weight ratio compared to those in the standard dose group (0.8 mg/day) [ 35 ].…”
Section: The Impact Of Periconceptional Folic Acid Supplementation On...mentioning
confidence: 99%
“…A randomized controlled trial (RCT) was performed to assess the effect of folic acid on fetal brain growth among pregnant women who smoke [ 35 ]. The results indicated that infants born to mothers who received high dose folic acid (4 mg/day) showed no difference in brain weight, but were 0.33 percentage points lower in brain/body weight ratio compared to those in the standard dose group (0.8 mg/day) [ 35 ].…”
Section: The Impact Of Periconceptional Folic Acid Supplementation On...mentioning
confidence: 99%